2000
DOI: 10.1017/s0022112000001798
|View full text |Cite
|
Sign up to set email alerts
|

Large-eddy simulation of a three-dimensional shear-driven turbulent boundary layer

Abstract: A three-dimensional shear-driven turbulent boundary layer over a flat plate generated by moving a section of the wall in the transverse direction is studied using large-eddy simulations. The configuration is analogous to shear-driven boundary layer experiments on spinning cylinders, except for the absence of curvature effects. The data presented include the time-averaged mean flow, the Reynolds stresses and their budgets, and instantaneous flow visualizations. The near-wall behaviour of the flow, which wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…This behavior is opposite of that found by Jung and Sung 12 for η = 0.5 and N = 0 and 0.429 but in agreement with previous numerical simulations of rotating pipes 37 and 3DTBL over a flat plate. 38 For 1.49 ≤ N ≤ 6.71, the rotor and stator boundary layers exhibit the main characteristics of 2DTBL except for the misalignment of the Reynolds shear stress and mean velocity gradient angles. These two boundary layers have then a more complex behavior in this range of swirl parameters in the narrow-gap case.…”
Section: Nature Of the Turbulent Boundary Layersmentioning
confidence: 97%
“…This behavior is opposite of that found by Jung and Sung 12 for η = 0.5 and N = 0 and 0.429 but in agreement with previous numerical simulations of rotating pipes 37 and 3DTBL over a flat plate. 38 For 1.49 ≤ N ≤ 6.71, the rotor and stator boundary layers exhibit the main characteristics of 2DTBL except for the misalignment of the Reynolds shear stress and mean velocity gradient angles. These two boundary layers have then a more complex behavior in this range of swirl parameters in the narrow-gap case.…”
Section: Nature Of the Turbulent Boundary Layersmentioning
confidence: 97%
“…The relationship between (1.5) and (1.6) will be discussed in § 3.2. In the present flow, the seminal numerical simulation was done by Kannepalli & Piomelli (2000) with the use of a wall-resolved large-eddy simulation (LES). They examined the effect of cross-flow for two different magnitudes of W S /U 0 = 0.3 and 1.0, where Re θ ≈ 1100 in their 3DTBL.…”
Section: ∂Wmentioning
confidence: 99%
“…They demonstrated that a half-power-law dependence in θ z /W s is intrinsically associated with the Stokes layer in which θ z ∼ t 1/2 . Kannepalli & Piomelli (2000) also discussed a possible scaling law of the spanwise skin friction coefficient C f ,z (defined in § 3.1) for W S /U 0 = 1 by comparing with the experimental data of Driver & Johnston (1990) (Re θ = 6000 in a trailing edge of the spinning cylinder). They used a normalization by U e W s /2ρ (see relation (4.1)).…”
Section: ∂Wmentioning
confidence: 99%
“…There has been continued effort is this area for several years (e.g. Kannepalli and Piomelli [45] and Chang et al [46]), but, to date, no significant progress has been made on practical models for CFD applications. Some promising advanced work by Cabot and Moin [47] used RANS models with additional consideration for unsteadiness and 'ejection' events.…”
Section: Turbulence: Additional Considerationsmentioning
confidence: 99%
“…Thus, most LES simulations use one of two approaches for wall boundary conditions: (a) no special treatment of the wall, except for additional grid points (Kannepalli and Piomelli [45]), and (b) wall-layer models essentially the same as used in RANS that have been shown, by Rodi et al [50], to give reasonably good results. For engine applications, the use of wall functions is probably the best approach for the near future.…”
Section: Turbulence: Additional Considerationsmentioning
confidence: 99%